Internal structure of intonational categories: The (dis)appearance of a perceptual magnet effect - Rodd, Joe; Chen, Aoju (Frontiers in Psychology, 2023)
The question of whether intonation events are speech categories like phonemes and lexical tones has long been a puzzle in prosodic research. In past work, researchers have studied categoricality of pitch accents and boundary tones by examining perceptual phenomena stemming from research on phoneme categories (i.e., intonation boundary effects—peaks in discrimination sensitivity at category boundaries, perceptual magnet effects—sensitivity minima near the best exemplar or prototype of a category). Both lines of research have yielded mixed results. However, boundary effects are not necessarily related to categoricality of speech. Using improved methodology, the present study examines whether pitch accents have domain-general internal structure of categories by testing the perceptual magnet effect. Perceived goodness and discriminability of re-synthesized productions of Dutch rising pitch accent (L*H) were evaluated by native speakers of Dutch in three experiments. The variation between these stimuli was quantified using a polynomial-parametric modeling approach. A perceptual magnet effect was detected: (1) rated “goodness” decreased as acoustic-perceptual distance relative to the prototype increased (Experiment 1), and (2) equally spaced items far from the prototype were more frequently discriminated than equally spaced items in the neighborhood of the prototype (Experiment 2). These results provide first evidence for internal structure of pitch accents, similar to that found in color and phoneme categories. However, the discrimination accuracy gathered here was lower than that reported for phonemes. The discrimination advantage in the neighborhood far from the prototype disappeared when participants were tested on a very large number of stimuli (Experiment 3), similar to findings on phonemes and different from findings for lexical tones in neutral network simulations of distributional learning. These results suggest a more transient nature of the perceptual magnet effect in the perception of pitch accents and arguably weaker categoricality of pitch accents, compared to that of phonemes and in particular of lexical tones.